Peran Partai Koalisi dalam Pengisian Kekosongan Jabatan Wakil Walikota Padang Sisa Masa Jabatan Periode 2019-2024 - Nurhadi, Nabila Annisa (Sekretariat Jenderal DPR RI, 2024)
Deputy regional heads have duties and functions to assist the running of a government.Following the election of Hendri Septa as the definitive Mayor of Padang City, replacingMahyeldi Ansharullah who won the 2021 regional election for Governor of West Sumatra,the position of Deputy Mayor of Padang for the 2019–2024 period remained vacant for twoyears. The process of filling vacancy for the Deputy Mayor position, which remained stagnantfor two years, raised significant question about the role of the coalition parties in carrying outthe process. This study aims to analyze the role of coalition parties in the process of fillingthe vacancy for the Deputy Mayor of Padang City for the remainder of the 2019-2024 termusing the John Gaventa's power cube theory. This study used a qualitative approach with acase study design, collecting data through interviews. The findings showed that the coalitionparties played role in driving the election process in the Padang City DPRD. The processwas hampered for due to the difficulty in reaching a consensus between the coalition parties,namely PAN and PKS, which prioritized their own power rights. However, at the end of2022 until the beginning of 2023 the process of filling the vacant position of Deputy Mayorof Padang City began to take place following the submission from each party. Currently, theelected Deputy Mayor of Padang City for the remaining term of 2019-2024 is Ekos Albarfrom PAN.